Copper photoredox catalyst "G1": a new high performance photoinitiator for near-UV and visible LEDs. Issue 36 (22nd August 2017) - Mokbel, H.; Anderson, D.; Plenderleith, R.; Dietlin, C.; Morlet-Savary, F.; Dumur, F.; Gigmes, D.; Fouassier, J.-P.; Lalevée, J.
Abstract : The goal of this paper concerns the development of photoinitiating systems usable in industrial processes for coating applications and the production of thick epoxy/glass fibre composites. Abstract : The goal of this paper concerns the development of photoinitiating systems usable in industrial processes for coating applications (cationic polymerization of epoxide based resins), the manufacture of Interpenetrating Polymer Networks (IPNs) (polymerization of acrylate/epoxy blends) and the production of thick epoxy/glass fibre composites. For these purposes, a copper photoredox catalyst, G1, is proposed as a high performance photoinitiator. It allows the design of very efficient three component photoinitiating systems (G1/iodonium salt (Iod)/ N -vinylcarbazole (NVK)). The effects of the resin, light source (LED@375, 395, 405 nm, halogen lamp), G1 concentration, coating thickness (25 μm and 1.4 mm), water content, formulation stability and hydrolytic stability of the cured coatings were investigated. Examples of IPNs and glass fibre composites are provided. In the studied applications the G1/Iod/NVK system is much better than BAPO/Iod/NVK (BAPO – bis(2, 4, 6-trimethylbenzoyl)phenylphosphine oxide – Irgacure 819) used as a reference system with good reactivity in the 365–420 nm range. Owing to the catalytic nature of G1, a reduced G1 content (30 fold less compared to the BAPO content) still leads to a higher practical efficiency than BAPO in the photopolymerization of a coating. A comparison with other reference systems based on 2-isopropylthioxanthone or anthracene is also provided and outlines again the very high performance of G1 for industrial applications.